2021
DOI: 10.1016/j.apsb.2021.01.013
|View full text |Cite
|
Sign up to set email alerts
|

In situ triggering antitumor efficacy of alcohol-abuse drug disulfiram through Cu-based metal-organic framework nanoparticles

Abstract: Although approved as an alcohol-abuse drug, disulfiram (DSF) exhibited potential anticancer activity when chelated with copper (Cu). However, the low level of intrinsic Cu, toxicity originated from exogenous Cu supplementation, and poor stability of DSF in vivo severely limited its application in cancer treatment. Herein, we proposed an in situ DSF antitumor efficacy triggered system, taking advantages of Cu-based metal-organic framework (MOF). In detail, DSF was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…1(g)). 40 Based on these results, it can be presumably demonstrated that Cu-MOF was successfully synthesized.…”
Section: Preparation and Characterization Of Cu-mofmentioning
confidence: 83%
See 1 more Smart Citation
“…1(g)). 40 Based on these results, it can be presumably demonstrated that Cu-MOF was successfully synthesized.…”
Section: Preparation and Characterization Of Cu-mofmentioning
confidence: 83%
“…In this process, the Cu-MOF was constructed referring to the previous study reported by Hou et al via a simple self-assembly method using Cu 2+ and organic linkers 2-MI. 40 Then, the morphology and structure of the prepared Cu-MOF were visualized on TEM and SEM. The results showed that the Cu-MOF had a nearly spindle distribution and exhibited a rough surface (Fig.…”
Section: Preparation and Characterization Of Cu-mofmentioning
confidence: 99%
“…85 DSF-Cu-MOF materials have recently been tested to release DSF but their main focus is in tumour therapies since DSF-copper chelate complexes have shown anti-cancer activity. 86 Thus, Hou et al 87 showed that Cu-MOFs loaded with DSF maintained the stability of Cu 2+ in the blood circulation and once accumulated at the tumour site, DSF-Cu-MOF particles internalize into tumour cells through endocytosis to release DSF and Cu 2+ simultaneously into the intracellular tumour microenvironment which is enriched with hyaluronidase. Consequently, an in situ chelation reaction occurs between DSF and Cu 2+ , generating a toxic DSF/Cu complex against tumour cells.…”
Section: Biological Applicationsmentioning
confidence: 99%
“…It has been reported that DTC can chelate Cu 2+ to form a bis­(diethyldithiocarbamate)–copper (CuET) complex, which exhibits a more significant antitumor effect than the original DSF . Currently, most reported work on the codelivery of DSF and Cu 2+ has been carried out by loading DSF into a Cu-containing metal–organic framework (MOF). However, these materials often lack the ability to target tumor tissues, are susceptible to clearance by the immune system, and possess a singular functionality, unable to respond intelligently to the tumor microenvironment (TME). Therefore, the development of a multifunctional nanosystem with good biocompatibility, capable of efficiently delivering DSF and Cu 2+ to tumor tissues while intelligently responding to the TME, along with tumor-targeting and immune escape capabilities, holds significant research and clinical application prospects …”
Section: Introductionmentioning
confidence: 99%